Mental Health Literate in the Context of Educational Technology: A Bibliometric Review of Instruments from 2014 to 2024 - Ardani, Tristiadi Ardi; Hanurawan, Fattah; Muslihati; Indreswari, Henny; Kususanto, Prihadi Ditto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study aims to provide insight into the status of research, the mapping process, annual themes of mental health literacy research, and offer relevant references. There are three stages of research: first, descriptive statistical analysis for data collection using publish and perish analysis and bibliometric R application, second, using quantitative methods for citation analysis using bibliometric R, and third, using qualitative methods to identify key research streams. The data used was based on the Scopus database. Keywords 'mental health' and literacy. Year of publication between 2014-2024. There were 3,456 articles, 1,256 journals and books, the number of citations per year per document was 2,656. The highest number of publications was in 2023 with 606 publications. Further research is recommended to explore the development of mental health literacy research literature and conduct a comparative study between.